2023
DOI: 10.1158/1078-0432.ccr-23-0099
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class II Loss and JAK1/2 Deficiency Coevolve in Melanoma Leading to CD4 T-cell and IFNγ Cross-Resistance

Abstract: Purpose: Recent studies have demonstrated HLA class II (HLA-II)-dependent killing of melanoma cells by cytotoxic CD4 T cells. We investigated evolution of HLA-II-loss tumors that escape cytotoxic CD4 T cell activity and contribute to immunotherapy resistance. Experimental Design: Melanoma cells from longitudinal metastases were studied for constitutive and interferon-inducible HLA-II expression, sensitivity towards autologous CD4 T cells, and immune evasion by HLA-II loss. Clinical significance of HLA-II-low t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…49 However, a later study found that melanoma cells prior to ICB had IFN-γ-inducible or constitutively expressed HLA class II, and these cells were sensitive to CD4 + T cellmediated killing in vitro. 50 Interestingly, after ICB treatments, the expression of HLA class II in these melanoma cells was lost, together with the loss of JAK/STAT signaling components. These results suggested the potential role of CD4 + T cells in the immune surveillance against melanoma cells and an important mechanism of immune resistance in melanoma cells against CD4 + T cells following ICB.…”
Section: Ipilimumab Blocks the Interaction Between Coinhibitory Moleculementioning
confidence: 98%
“…49 However, a later study found that melanoma cells prior to ICB had IFN-γ-inducible or constitutively expressed HLA class II, and these cells were sensitive to CD4 + T cellmediated killing in vitro. 50 Interestingly, after ICB treatments, the expression of HLA class II in these melanoma cells was lost, together with the loss of JAK/STAT signaling components. These results suggested the potential role of CD4 + T cells in the immune surveillance against melanoma cells and an important mechanism of immune resistance in melanoma cells against CD4 + T cells following ICB.…”
Section: Ipilimumab Blocks the Interaction Between Coinhibitory Moleculementioning
confidence: 98%